CRITICAL EDUCATION WITH CULTURAL IDEOLOGICAL DIMENSIONS - Anak Agung Gde Putera Semadi (Universitas Pendidikan Ganesha, 2021)
In an effort to develop cultured critical education, the concept of education needs to be formulated as a process of cultural dimension/humanization process. The process of education cannot be separated from human life in the context of cultural creation as well as its inheritance (cultural creation and cultural transmission) to the young generation. Through the process of critical education, humans are able to develop various potentials or creations, tastes, initiatives, and works that are at the core of the cultural process, because culture in the essential concept of education can be formulated as